Surveillance of chronic diseases: Challenges and strategies for India - Udaya S. Mishra; Sebastian Irudaya Rajan; William Joe; Ali Mehdi (Indian Council for Research on International Economic Relations (ICRIER), 2016)
This paper describes the status, challenges and scope for strengthening surveillance of chronic disease risk factors, morbidities and mortality in India. We draw upon the surveillance experience of four selected States of India namely Uttar Pradesh, Rajasthan, Kerala and Tamil Nadu to understand key requirements in relation to financing, infrastructure, human resources and governance. The public health system is grappling with resource constraints but there is room for more efforts to undertake systematic population-based chronic disease surveillance in India. Although there are no immediate policy goals to ensure population-based screening, opportunistic screening of selected chronic diseases is an important strategy under the National Programme for Prevention and Control of Diabetes, Cardiovascular diseases and Stroke (NPCDCS). However, surveillance activities under this programme are performing suboptimally due to issues related to funding constraints, operational guidelines and inadequate clinical, technical and managerial staff. It is apparent that public health system should devote additional resources towards active population-based surveillance. Besides financing, there is a need to develop institutional mechanisms for engagement of adequate human resources for surveillance and disease management. Engagement of AYUSH and community health workers (ASHAs or others) is identified as reasonable options but would require sound incentive mechanism to ensure good coverage and programme outreach. Furthermore, local support, both social and political, is critical to create a conducive environment to contact beneficiaries and for information recording. In this endeavour, private sector is identified as a potential partner that needs enabling environment to come up with services under PPP.
Keywords: C8; I18; 330; Surveillance; chronic diseases; risk factors; morbidity; mortality